RATON SUGAR CANE PRODUCTIVITY RECOVERING WITH NPK FERTILIZATION - WEBER, Heroldo; DAROS, Edelclaiton; ZAMBON, José Luiz Camargo; IDO, Oswaldo Teruyo; BARELA, José Donisete (Scientia Agraria, 2001)
With the objective of evaluating the influence of the fertilization on the raton productivity that had not been fertilized in the previous courts, two trials were done to field, in soil Latossolo Roxo, in Usina Casquel, Cambará, PR. The experimental design was randomized complete blocks, with five replications to application of eight treatments, with experimental units of 5 rows of 15 m of length and spacing among rows of 1.3 m. The treatments were only N (0, 50, 100 and 150 kg.ha-1), the association of N and K (100 kg.ha-1 N with 50, 100 and 150 kg.ha-1 K2O) and the association of NPK (100 kg.ha-1 N + 100 kg.ha-1 K2O +100 kg.ha-1 P2O5). The results obtained in sugar cane of 3rd raton, show that the recovery of the agricultural productivity reached yields of 48.5% and 34.4% with the application of the recommended fertilization, having N and K, respectively, for the areas where the treatments were applied to the 70 and 90 days after harvesting. In one of trials the reapplication of the treatments, in 4th ratoon, 45 days after harvesting, presented increments in the productivity of up to 76.2%.